Crown Store - Jehad Abdalhaq; Abdullah Jawabreh (My University, 2025)
Crown Store is an online store specializing in men's clothing. It aims to provide a unique, elegant, and user-friendly shopping experience that combines modern design, speed, and ease of use. The website features a clear and seamless user interface, allowing customers to browse products with ease. They can dynamically select available sizes and colors for each product based on actual inventory, ensuring a fast and accurate shopping experience. The system also offers the ability to track orders after purchase, sending automatic notifications to customers, enhancing their confidence and satisfaction. It also supports a variety of secure payment options. The user experience has been intelligently customized by displaying products in clear, modern images. A product exchange and return form has been developed using Contact Form 7, allowing customers to easily select the product they want to exchange and specify its associated features. The project aims to provide a professional e-commerce platform that meets customer needs, ensures ease of management for the team, and delivers a superior user experience that contributes to promoting the brand and its wider market reach. Thank you.